A Shout in the Sunshine - Ioannides, Mara W. Cohen (Book collections on Project MUSE., 2007)
In fifteenth century Greece, an extraordinary friendship develops between Miguel, a refugee from post-Inquisition Spain, and David, the son of a wealthy Greek fabric merchant, despite the concerns of both Greek and Spanish Jews that the other group is not truly Jewish.